Metodología para la administración de proyectos: Una nueva cultura de trabajo = Methodology for Project management: A new labor attitude). - Mendoza, M. (Facultad de Contaduría Pblica y Administracin U.A.N.L., 2007)
Abstract. Projects are crucial for the success of the organizations. The projects produce products, services, environment, processes and new or improved organizations. Furthermore, the projects increase sales, improve the satisfaction level of the clients, reduce the costs, and better the hob environment and so forth. Through this research paper the benefits of adopting a methodology that serves as a guide for Project management is discussed in detail. The most relevant benefit for the organization would be to deliver the product based upon the client necessities and requirements. The most important issues are as follows. 1. The methodology for project management imlies a change in attitude. 2. The time dedicated for the implementation and training for this kind of work constitutes the key factor for the success or failure of the project. 3. To homogenize the terminology, the organizations will declare indicators for each job leader. 4. The communication among the organizational members are truly important.